Water Cladded Plasmonic Slot Waveguide Vertically Coupled With Si3N4 Photonics - George Dabos; Dimitra Ketzaki; Athanasios Manolis; Evaggelia Chatzianagnostou; Laurent Markey; Jean-Claude Weeber; Alain Dereux; Anna Lena Giesecke; Caroline Porschatis; Bartos Chmielak; Dimitris Tsiokos; Nikos Pleros (IEEE Photonics Journal, 2018)
We demonstrate a water cladded plasmo-photonic waveguide, by exploiting the directional coupling scheme to vertically divert light from a 360 × 800 nm (height × width) Si3N4 waveguide to a plasmonic slot waveguide, enabling the excitation of a pure plasmonic mode within a 210-nm-wide slot at 1550 nm. The 150-nm-thick plasmonic slot waveguide was deposited on the top of an oxide cladded Si3N 4 waveguide exhibiting an experimental plasmonic-to-photonic insertion loss of 2.24 ± 0.3 dB and a plasmonic propagation length (Lspp) of 10.8 μm at 1550 nm. The proposed plasmo-photonic waveguide holds a promise as an optical transducer element for highly sensitive and low-cost interferometric biosensors due to the significant phase change achieved per unit propagation length.